Hyperammonemia increases the release of pathological extracellular vesicles from monocytes by impairing lysosomal function and autophagy through the TNFα–cAMP–PKA–LC3 pathway - Pedrosa, Maria A.; Izquierdo-Altarejos, Paula; Llansola, Marta; Felipo, Vicente (Frontiers in Immunology, 2026)
BackgroundPatients with liver cirrhosis may show minimal hepatic encephalopathy (MHE) triggered by a shift in peripheral inflammation. A main mechanism by which peripheral alterations are transmitted to the brain is the infiltration of extracellular vesicles (EV). Hyperammonemic rats are a model of MHE that reproduces cognitive impairment. Injection of EV from plasma or peripheral blood mononuclear cells (PBMC) of hyperammonemic rats to normal rats induces neuroinflammation, alterations in neurotransmission, and cognitive impairment. PBMC contain different cell types. The aims were 1) to identify which cell type produces the pathological EV in hyperammonemic rats; 2) to identify the mechanisms by which hyperammonemia increases EV release from monocytes and induces the formation of pathological EV; and 3) to analyze the role of TNFα and PKA in these mechanisms.MethodsEV were isolated from primary cultures of CD4+ lymphocytes or monocytes from control or hyperammonemic rats and added to hippocampal slices from control rats to assess induction of neuroinflammation and changes in neurotransmission. To assess the role of TNFα and protein kinase A (PKA) in the production of pathological EV by monocytes from hyperammonemic rats, we blocked TNFα with anti-TNFα or inhibited PKA. Lysosomal-autophagy dysfunction was assessed with LysoTracker and by analyzing cathepsin L, LAMP2, and LC3.ResultsIn hyperammonemic rats, monocytes but not CD4+ lymphocytes release pathological EV. Hyperammonemia increases the EV release by monocytes and their content of TNFR1 and TNFα. These EV induce activation of glia and of the TNFα–TNFR1–S1PR2−IL-1β–CCL2–BDNF–TrkB pathway and alterations in membrane expression of NMDA and AMPA receptors in hippocampal slices from control rats. Hyperammonemia increases TNFα levels in monocytes, which increases cAMP and PKA activity and reduces LC3 content. This leads to autophagy–lysosome dysfunction, with altered LC3, cathepsin L, and LAMP2 content and pH that increases the release of EV and their TNFR1 and TNFα content. All these changes are reversed by blocking TNFα with anti-TNFα or inhibiting PKA with an inhibitor.ConclusionsThese data unveil that monocytes produce the pathological EV in hyperammonemia and the underlying mechanisms and provide the bases for new treatments to improve cognitive and motor function in hyperammonemia and MHE.